2009
DOI: 10.1086/596499
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Breast‐Feeding in the Prevention ofHelicobacter pyloriInfection: A Systematic Review

Abstract: Breast-feeding is protective against H. pylori infection, especially in middle- and low-income nations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 40 publications
3
29
0
3
Order By: Relevance
“…A retrospective serological study by Blecker et al in a developed country showed that a small portion of the population acquired H. pylori infection (< 1%) during the 1st year of life (22). Acquisition of H. pylori infection usually occurs during the first 5 years of life (23).…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective serological study by Blecker et al in a developed country showed that a small portion of the population acquired H. pylori infection (< 1%) during the 1st year of life (22). Acquisition of H. pylori infection usually occurs during the first 5 years of life (23).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that breastfeeding is protective against the acquisition of H. pylori infection [31][32][33], while other studies have reported no protective effect of breastfeeding [3,5,34]. Prevalence of H. pylori infection in children breastfed longer than 12 months was lower than those breastfed for a shorter duration [OR (95% CI): 0.58 (0.35-0.94)] (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…However, vaccine studies using mice lacking IgA or even all mature B cells have shown that vaccineinduced protection against Helicobacter infection in such mice is comparable to that in vaccinated wild-type mice (Ermak et al, 1998;Blanchard et al, 1999). As mentioned previously, H. pylori-specific SIgA antibodies in breast milk have been shown to be associated with protection against colonization in breast-fed children (Bhuiyan et al, 2010;Chak et al, 2009), which may suggest that partly different protective mechanisms might exist in mice and humans. It is noteworthy, however, that protection in the vaccinated mice lacking mature B cells is accompanied by more severe gastritis compared to similarly vaccinated wild-type mice, indicating that B cells, as suggested previously, might have an anti-inflammatory regulatory role in the stomach during H. pylori infection (Akhiani et al, 2004) (Figure 2).…”
Section: Lessons Learnt From Animal Modelsmentioning
confidence: 89%
“…A birth cohort study in Bangladesh showed that infants fed on breast milk containing high titers of H. pylori membrane protein-specific IgA antibodies had a significant delay in acquisition of H. pylori infection compared to infants fed on low-titer breast milk (Bhuiyan et al, 2010). A systematic analysis of studies on the role of breast-feeding in H. pylori infection has shown that breast-feeding can indeed protect against acquisition of new H. pylori infection, particularly in children in low-and middle-income countries (Chak et al, 2009). Further support for a protective role of SIgA antibodies came from a study showing that, whereas H. pylori infection in WT mice was spontaneously eradicated from the duodenum after three months, knockout mice lacking polymeric Ig receptor were abundantly colonized with H. pylori in the duodenum (Gorrell et al, 2013).…”
Section: Adaptive Immune Responsesmentioning
confidence: 99%